DETERMINANTS OF STUDENT’S SATISFACTION IN EDUCATION QUALITY AT VIETNAM NATIONAL UNIVERSITY OF FORESTRY IN THE PERIOD 2015-2016 - Van Quy, Khuc; Quang Bao, Tran (Journal of Forestry Science and Technology, 2016)
This research aimed at evaluating the student’s satisfaction level (SSL) in education quality at Vietnam National University of Forestry (VNUF), a leading university for generating high-quality human resources in the field of forestry of the country. The study team used questionnaires to gather data from 345 students, at the main campus in Hanoi capital and at the second campus in Dong Nai province, in August and September 2015. The Explorary Factor Analysis (EFA) method and Linear Regression (LR) model were employed to determine the factors influencing SSL. The results have shown that the student’s satisfaction in education quality at VNUF is fairly high, getting GPA of 3.47/5; lecturers, study environment and student’s services are of three most important factors affecting the student’s satisfaction. The findings of research helped find fundamental solutions to improve education quality and help VNUF become multisectoral, advanced and modern university in coming years.